Sewa Menyewa Tanah Warisan Tanpa Izin Ahli Waris Yang Lain - Julkipli Sameth; Merry Tjoanda; Sabri Fataruba (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: Therefore, if one of the heirs makes a transaction on the inheritance, they must obtain permission or approval from the other heirs. However, in reality there are still heirs who carry out transactions on inheritance without permission or approval from other heirs, as happened in the case of land leases carried out by Johanis Salamahu and Mrs. Magdalena Peilaouw with PT Haka Aston, where Johanis did not involve heirs. Other, The method used in this paper is a normative juridical method with a statutory approach and a conceptual approach. The results of the study show that there is no regulation that specifically regulates the procedure for leasing land which is jointly owned by the heirs. However, in general, the things that should be considered are that the agreement must be known to all heirs, the existence of a power of attorney for the heirs for someone who is given the right to lease the inherited land, the existence of the area, address and location of the object of the agreement, the time period, the agreed price, and land use. While the legal consequences arising from the existence of an Inherited Land Lease Agreement by one of the heirs with PT Haka Aston without the knowledge of the other heirs, namely the agreement must be declared null and void because objective conditions are not met, namely a certain matter. One thing is certain, namely the rights and obligations of the other heirs are not fulfilled, because the land which is the object of the lease is jointly owned by the heirs, so to be able to lease it, you must obtain permission or approval from the other heirs.